A model assessment of the importance of direct photolysis in the photo-fate of cephalosporins in surface waters: Possible formation of toxic intermediates. (September 2015) - Fabbri, Debora; Minella, Marco; Maurino, Valter; Minero, Claudio; Vione, Davide
Graphical abstract: Highlights: Cephalosporins are transformed in surface waters by hydrolysis and photochemistry. Photochemistry would prevail in waters with low depth and/or low DOC. Important direct photolysis for cefazolin, negligible for cefradine and cefalexin. Direct photolysis is favoured in shallow waters with intermediate/high DOC values. Such conditions favour the formation of toxic intermediates. Abstract: The direct and indirect photodegradation of six cephalosporins was predicted using a photochemical model, on the basis of literature values of photochemical reactivity. Environmental photodegradation would be important in surface water bodies with depth ⩽2–3 m, and/or in deeper waters with low values of the dissolved organic carbon (DOC ⩽ 1 mg C L −1 ). The half-life times would range from a few days to a couple of weeks in summertime. In deeper and higher-DOC waters and/or in different seasons, hydrolysis could prevail over photodegradation. The direct photolysis of cephalosporins is environmentally concerning because it is known to produce toxic intermediates. It would be a major pathway for cefazolin, an important one for amoxicillin and cefotaxime and, at pH < 6.5, for cefapirin as well. In contrast, direct photolysis would be negligible for cefradine and cefalexin. The DOC values would influence the fraction of photodegradation accounted for by direct photolysis in shallow water, to a different extent depending on the role of sensitisation by the triplet states of chromophoric dissolved organic matter.